Radioscaphoid Pressures and Carpal Kinematics After Wrist Ligament Sectioning - Eswaran, Sanju P.; Short, Walter H.; Werner, Frederick W. (Journal of Wrist Surgery, 2025)
Scapholunate dissociation is usually the result of failure of multiple wrist ligaments. With continued use other structures attenuate, which results in change in position of the carpal bones. It is presumed that load characteristics in the wrist joint change with changes in carpal bone position. This is thought to result in localized pressure overload and arthritic change.The purpose of this study was to evaluate radioscaphoid joint pressures and carpal kinematics after sectioning specific wrist ligaments. Our hypotheses are that there would be increased scaphoid flexion and ulnar deviation, increased lunate extension and radial deviation, increased contact pressure in the radioscaphoid fossa, and increased tendon forces.Eight cadaver wrists were instrumented with an electromagnetic motion tracking device and a pressure sensor was inserted into the radioscaphoid joint. Using a wrist joint motion simulator, motion and pressure data were obtained in the moving wrist in the intact state and after sectioning the dorsal radiocarpal, dorsal intercarpal, and scapholunate interosseous ligaments.After ligament sectioning there was increased scaphoid flexion, scaphoid ulnar deviation, lunate extension, and lunate radial deviation resulting in carpal instability. There was also an increase in pressure in the radioscaphoid fossa. Several specimens showed evidence of scaphoid subluxation.It is our conclusion that this combination of ligament sectioning produces scapholunate instability and increased pressures in the radioscaphoid fossa in the laboratory setting. We believe that if left untreated in the clinical setting, scapholunate advanced collapse could result.
Keywords: scapholunate interosseous ligament sectioning; scapholunate dissociation; scapholunate interosseous ligament; carpal kinematics; radioscaphoid fossa pressures